2015
DOI: 10.1155/2015/396593
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Electromagnetic Field Conditioning Protects against I/R Injury and Contractile Dysfunction in the Isolated Rat Heart

Abstract: Low frequency electromagnetic field (LF-EMF) decreases the formation of reactive oxygen species, which are key mediators of ischemia/reperfusion (I/R) injury. Therefore, we hypothesized that the LF-EMF protects contractility of hearts subjected to I/R injury. Isolated rat hearts were subjected to 20 min of global no-flow ischemia, followed by 30 min reperfusion, in the presence or absence of LF-EMF. Coronary flow, heart rate, left ventricular developed pressure (LVDP), and rate pressure product (RPP) were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…Continuing the hypothesis that electromagnetic field may be used as a therapeutic agent 26,27 and following the study of Ma et al, 25 who demonstrated the inhibition of ROS generation by LF-EMF, we showed the cardioprotective role of LF-EMF in ex vivo model of cardiac I/R. 18 Cardiomyocytes are highly specialized, high-oxygen-requiring cells with large number of mitochondria. They occupy nearly 75% of the cardiac mass, but make only about one-third of the total cell number in the heart.…”
Section: Discussionsupporting
confidence: 64%
“…Continuing the hypothesis that electromagnetic field may be used as a therapeutic agent 26,27 and following the study of Ma et al, 25 who demonstrated the inhibition of ROS generation by LF-EMF, we showed the cardioprotective role of LF-EMF in ex vivo model of cardiac I/R. 18 Cardiomyocytes are highly specialized, high-oxygen-requiring cells with large number of mitochondria. They occupy nearly 75% of the cardiac mass, but make only about one-third of the total cell number in the heart.…”
Section: Discussionsupporting
confidence: 64%
“…In total, 32 male Wistar rats (250‐350 g, 3 months of age) originating from the University of Liège animal facility (Federal authorization for breeding animals LA1610002) were kept in a pathogen‐free (SPF) facility, at least two per ventilated cages in a controlled temperature and regular light/dark cycle. The non‐invasive tail–cuff method used to measure BP has been extensively described as an adequate method for the estimation of BP and routinely used in our lab (Bialy et al , ; Dogne et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…A beneficial effect of PEMF exposure on hypoxia-related conditions has been found through inhibition of hypoxia/reoxygenation-induced death of human renal proximal tubular cells via suppression of intracellular reactive oxygen species (ROS) production [ 33 ]. Moreover, it has been demonstrated that electromagnetic fields when applied prior to, during, and after the ischemic insult protect the heart against ischemia/reperfusion-induced cardiac contractile dysfunction and heart injury [ 34 ]. In acute experimental myocardial infarcts in rats, PEMFs were able to limit the area of necrosis caused by ischemic injury [ 35 ].…”
Section: Introductionmentioning
confidence: 99%